PENGARUH PENDEKATAN SAINTIFIK BERBANTUAN MEDIA VIDEO DAN MOTIVASI TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS V SEKOLAH DASAR - Sirait, Hotmaida Rotua; Napitupulu, Efendi; Darmana, Ayi (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2023)
The aim of this research is to: Examine how fifth grade students at SD Negeri 2, Kualuh Hulu District, learned mathematics using scientific techniques aided by audiovisual technology. People living in Kualuh Hulu Regency's SD Negeri Region 2.  The number of schools is 63 schools. The research sample was 60 students of SD Negeri No. 112279 Aek. A sample of 30 students were taught using a scientific learning approach (Experiment/A1) with video assistance, and 30 students were taught using a contextual learning approach (Control/A2) without video assistance. The research instruments are tests and questionnaires to differentiate student motivation. This research uses a 2 x factorial design. The research findings passed the homogeneity and normality tests which are prerequisites for analysis. Hypotheses can be tested using Two Way Analysis of Variance, often known as Two Way Anova. The study concludes that a scientific strategy using video media influences students' learning results in mathematics at SD Negeri Region 2 Kualuh Hulu Regency.